2006
DOI: 10.1002/lt.20792
|View full text |Cite
|
Sign up to set email alerts
|

Conversion from mycophenolate mofetil to enteric-coated mycophenolate sodium in liver transplant patients presenting gastrointestinal disorders: A pilot study

Abstract: Gastrointestinal (GI) disorders are one of the main adverse events in patients treated by mycophenolic acid (MPA). The aim of this prospective study was to evaluate the effect of conversion from mycophenolate mofetil (MMF) to enteric-coated mycophenolate sodium (EC-MPS) in liver transplant patients presenting GI side-effects Since January 2003, stable liver transplant patients receiving MMF and presenting GI disorders, without evidence of other origin than MMF were enrolled. Conversion was performed without a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
0
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 21 publications
1
24
0
2
Order By: Relevance
“…Patients enrolled in this study were assessed at baseline and visit 2 (4–6 wk post‐baseline) with a series of questionnaires which showed a decrease in the intensity of the GI side‐effects and an improvement in the patients QoL. EC‐MPS has been shown to be safe in both adult and pediatric liver recipients converted away from MMF, but this study did not use QoL questionnaires to analyze the impact of the conversion (11).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients enrolled in this study were assessed at baseline and visit 2 (4–6 wk post‐baseline) with a series of questionnaires which showed a decrease in the intensity of the GI side‐effects and an improvement in the patients QoL. EC‐MPS has been shown to be safe in both adult and pediatric liver recipients converted away from MMF, but this study did not use QoL questionnaires to analyze the impact of the conversion (11).…”
Section: Discussionmentioning
confidence: 99%
“…Patients enrolled in this study were assessed at baseline and visit 2 (4-6 wk post-baseline) with a series of questionnaires which showed a decrease in the intensity of the GI side-effects and an improvement in the patients QoL. EC-MPS has been shown to be safe in both adult and pediatric liver recipients converted away from MMF, but this study did not use QoL questionnaires to analyze the impact of the conversion (11). In our single center, open label study, conversion from MMF to EC-MPS has shown a statistically significant improvement in GI-related QoL in recipients of OLT with GI intolerability, with the exception of the emotional subscale at months 3 and 12.…”
Section: Discussionmentioning
confidence: 99%
“…Immunosuppressive regimens containing mycophenolate mofetil (MMF), a prodrug of mycophenolic acid (MPA), have shown efficacy in adult liver transplant recipients 1–3. Recently, enteric‐coated mycophenolate sodium (EC‐MPS), a new formulation of MPA, has shown a reduction of gastrointestinal disorders in comparison with MMF 4. MPA prevents the proliferation of both T and B lymphocytes by selectively and reversibly inhibiting type II inosine monophosphate dehydrogenase (IMPDH), a key enzyme in the de novo pathway of purine synthesis 5…”
mentioning
confidence: 99%
“…1 We agree that many 1-way conversion trials have been reported to be initially successful, and subsequently, not to be confirmed. Nevertheless, results of pilot studies can be considered as the first step of scientific demonstration of the efficacy of a new therapeutic strategy.…”
mentioning
confidence: 67%